Churnalism on the Rise?: Assessing convergence effects on editorial practices - Saridou, Theodora; Spyridou, Lia Paschalia; Veglis, Andreas A. (My University, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Scholars conceptualize journalism’s transformation and explain the changes occurring at different levels under the rubric of convergence. Contrary to optimistic views of convergence, claiming for its potential to satisfy both good journalism and good business practices, the paper argues that at times of economic uncertainty, hyper-competition and diminishing accountability levels, convergence is used as a cost-effective strategy fostering low-cost and spreadable news production. Engaging in quantitative analysis, the article provides empirical evidence showing that the recycling of news content from established elite sources and across popular news sites has increased between 2013 and 2016, posing serious threats for content plurality and independent reporting. Despite online journalism’s development as a field, and the appearance of social networks and user-generated content as alternative and easyily accessible sources, a pervasive survival and monetization culture has turned churning into a mainstream journalistic practice.
Keywords: churnalism; convergence; journalism; recycled news content sources; sourcing practices